Analyzing financial performance of resort and hotel subsector: A case study at Saung Dolken - Gibraltar, Muhammad Rais; Hermanto, Hermanto; Bandono, Bayu (International Journal Labs, 2024)
The COVID-19 pandemic has significantly disrupted the stability of global economic flows and threatened the business of companies in the world. The purpose of this study is to analyze the existing condition of the financial performance of Saung Dolken Resort and Hotel for the period 2018 to 2022 and benchmarking with the hotel sub-sector industry, analyze the level of potential bankruptcy (financial distress) of SDO in Indonesia during the Covid-19 period, and formulate a financial performance model. This study aims to find out what factors affect SDO's financial performance which is proxied with return on equity (ROE) based on independent variables from the Dupont analysis components, namely: ATO: asset turnover ratio, LEV: financial leverage, TaxB: tax burden, IntB: interest burden, OPM : operating profit margin, and EM : Equity Multiplier (EM) Adjustment. The study examines Saung Dolken Resort and Hotel's financial performance from 2018-2022 using descriptive analysis and Du Pont Analysis, identifying strengths and weaknesses for investors. The results show that the period before and during the co-incidence period showed a significant decrease in ROE caused by a decrease in ATO, Asset Turnover, and LEV, followed by an increase in TaxB and intB. The strategy includes profit margin optimization, asset turnover improvement, and equity multiplier adjustment.